A critical review of legal issues and solutions associated with building information modelling - Fan, Su-Ling; Lee, Cen-Ying; Chong, Heap-Yih; Skibniewski, Mirosław J. (Technological and Economic Development of Economy, 2018)
Although there are many discussions of the legal implications of BIM, none of the studies provides a comprehensive review of the legal issues associated with BIM; nor do they evaluate the solutions currently available to address the issues. This paper aims to provide a critical review of the legal issues arising from using BIM and of their associated solutions. A systematic review was conducted of fifty-five (55) journal articles and conference papers published from 2007 to 2017 to identify the legal issues. The identified legal issues were then analysed in relation to the solutions provided by the construction industry. The results of the study revealed that (1) an alternative project delivery approach that does not modify the original orientation of the design-bid-build procurement structure is required to deliver BIM effectively. (2) The potential change in the standard of care for project participants due to additional roles required in delivering BIM needs further investigation. (3) The roles for auditing a BIM delivery system must be included in the contracts to ensure the quality and compliance of BIM deliverables. The study not only reviews the legal issues associated with BIM, but more importantly, it also offers significant insights for future research.